2022
DOI: 10.1038/s41467-022-29855-8
|View full text |Cite
|
Sign up to set email alerts
|

Vasa nucleates asymmetric translation along the mitotic spindle during unequal cell divisions

Abstract: AbstractmRNA translation on the spindle is hypothesized to be an essential strategy for the localized production of cell regulators. This mechanism may be important particularly in early embryonic cells, which have a large diffusion volume and that undergo rapid cell divisions. Evidence to test such a hypothesis has been, however, limited. Here, we use an embryo with both symmetric and asymmetric cell divisions and manipulate Vasa protein, an RNA-helicase, on the spindle in live sea urchin embryos. We learned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…This region is evolutionarily conserved yet distinct from other DDX helicases (Fig. 4c) 9 , and was also recently reported to be critical for Vasa's function in embryonic cells of the sea urchin 22 . We, therefore, hypothesize the C3 region is critical for DDX4's activity in somatic cells.…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…This region is evolutionarily conserved yet distinct from other DDX helicases (Fig. 4c) 9 , and was also recently reported to be critical for Vasa's function in embryonic cells of the sea urchin 22 . We, therefore, hypothesize the C3 region is critical for DDX4's activity in somatic cells.…”
Section: Resultsmentioning
confidence: 56%
“…Especially in H69AR and SHP77 cells that share a mesenchymal morphology and are partially adherent, DDX4 is stained in the cytoplasm and on the mitotic apparatus. DDX4’s localization to the mitotic apparatus was previously seen in hematopoietic cancer cell lines 25 as well as sea urchin embryonic cells 20 , 22 , suggesting DDX4’s possible conserved function among various cells and organisms.
Fig.
…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…It was suggested that the defects in mitosis are not due to a global deficit of cyclin B protein, but rather, the localization of the cyclin B transcript and its local translation at the mitotic spindle itself is important for progression through mitosis (Groisman et al ., 2000). Since ribosomal proteins and RNAs are present at the mitotic spindle and in early cleavage stage embryos (Hassine et al ., 2020; Fernandez-Nicolas et al ., 2022), an intriguing possibility is that local translation of these transcripts encoding proteins that regulate mitosis may be essential for mitotic progression.…”
Section: Discussionmentioning
confidence: 99%